EVALUATION OF TREATMENT EFFECTIVENESS AND PATIENT SATISFACTION WITH THE USE OF EPSORA IN PSORIASIS MANAGEMENT AT FOB DERMATOLOGY CLINIC IN 2024 (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the treatment outcomes of E-psora and patient satisfaction in psoriasis at the FOB Dermatology Clinic in 2024.Methods: A cross-sectional study was conducted on 75 patients with mild to moderate plaque psoriasis treated at FOB Dermatology Clinic from January to October 2024. Treatment effectiveness was assessed using PASI and DLQI; satisfaction was measured with the Likert scale.Results: The mean PASI score significantly decreased from 6.97 to 2.13 (p
Keywords: psoriasis, treatment, satisfaction, E-psora.